Prenatal Ultrasound Diagnosis and Conservative Management of Fetal Lower Urinary Tract Obstruction with Bilateral Hydroureteronephrosis and Severe Oligohydramnios at 23 Weeks of Gestation: A Case Report - Jackson Mandala Putra; Abarham Martadiansyah; Nuswil Bernolian (Lembaga Publikasi Ilmiah Nusantara, 2026)
Fetal lower urinary tract obstruction (LUTO) is a rare group of congenital anomalies characterized by megacystis, bilateral hydroureteronephrosis, and, in severe forms, oligohydramnios that predisposes to pulmonary hypoplasia and renal dysplasia. This report described a 37-year-old multigravida (G3P2A0) referred at 23 weeks of gestation with intermittent abdominal pain and a suspected fetal anomaly. Serial fetal ultrasonography demonstrated bilateral hydronephrosis and hydroureter, a distended, thick-walled bladder with a keyhole sign suggestive of LUTO, and severe oligohydramnios (deepest vertical pocket 0.59 cm). Maternal renal function and infection screening were unremarkable. After multidisciplinary counseling regarding the guarded prognosis and the local unavailability of fetal therapy, expectant management was undertaken, comprising tocolysis with nifedipine, antenatal corticosteroids, maternal rehydration, and planned amnioinfusion with serial ultrasound surveillance. The patient stabilized and was discharged for close follow-up. This case underscored the central role of prenatal ultrasonography in early recognition of LUTO and the importance of severity-based, multidisciplinary counseling. When severe oligohydramnios presents in the second trimester, the prognosis is guarded, and standardized staging and timely referral to a fetal-therapy center are essential to optimize perinatal outcomes